THE INCIDENT OF ISRA' MI'RAJ FROM THE PERSPECTIVE OF PHYSICS - Fahrezha, Faizal; Muyassarah, Sifa; Annisa, Diya; Faqihuddin, Achmad (Academic Solution Publisher, 2024)
The Isra' and Mi'raj event is one of the important events in Islam, which is believed to be a miracle of the Prophet Muhammad. This event describes the Prophet Muhammad's journey from the Grand Mosque in Makkah to the Aqsa Mosque in Palestine, followed by a vertical journey to the sky to reach Sidratul Muntaha. Physically, the Isra' and Mi'raj event is a phenomenon that is difficult to explain. The journey from Makkah to Palestine takes at least 12 hours, while the vertical journey to the sky to Sidratul Muntaha takes much longer. In addition, the speed of light is the highest speed limit in the universe, so traveling at the speed of light or faster is impossible. Nonetheless, some physicists have tried to provide an explanation for the Isra' and Mi'raj events. One of the theories put forward is Heisenberg's uncertainty theory, which states that the position and momentum of an object cannot be known with certainty simultaneously. This theory can be used to explain how the Prophet Muhammad could be present in many places at almost the same time. Another theory put forward is the theory of annihilation, which states that energy can turn into light. This theory can be used to explain how the Prophet Muhammad could experience the process of purifying the heart. However, both theories still have limitations. Heisenberg's uncertainty theory cannot explain how the Prophet Muhammad could travel at a speed faster than the speed of light. Meanwhile, the theory of annihilation cannot explain how the heart purification process can turn the Prophet Muhammad into light. In conclusion, the Isra' and Mi'raj events are phenomena that cannot be fully explained by human science. This event is a miracle that can only be understood with faith.